Virtual Ethnography of TikTok Social Media Users' Comments on Lina Mukherjee's Account - Raihan, Muhammad Fajar; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2024)
The amount of content on social media makes netizens give various kinds of comments on the content without paying attention to the ethics of commenting, just like what happened in Lina Mukherjee's Tik Tok content. This research aims to find out how hate comments exist on Lina Mukherjee's TikTok account through a virtual ethnographic approach. This type of research is qualitative through a virtual ethnographic approach using observation and literature study as a data collection technique. The data that has been collected is then analyzed using the Miles and Huberman analysis technique. The results of the study show that in the content of Lina Mukherjee's video that has reaped a lot of controversy, namely the video of reviewing Balinese pork guling food invites netizens to comment, but these comments are dominated by negative comments, only a few comments are positive, and neutral comments. The number of negative comments shows that some netizens do not apply communication ethics when commenting, so it is necessary to implement efforts to implement communication ethics which includes 6 steps, namely: Use good language; Do not use words that are vulgar, provocative, pornographic or SARA; cross-check the truth of the news; do not make honest uploads and do not spread false information; do not copy or use copyrighted articles or images without permission; and provide comments that are in accordance with the topic of the upload on social media.